PEMBELAJARAN MENDALAM SEBAGAI STRATEGI PENGUATAN PENDIDIKAN INKLUSIF BAGI ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH DASAR - Enny Khoirun Nihaya; Tri Joko Raharjo; Liftiah; Ali Formen (STKIP Subang, 2026)
Inclusive education is an effort to provide equal educational services for all students, including children with special needs. In its implementation, inclusive education requires learning strategies that are able to accommodate the diverse characteristics and learning needs of students. One approach that can support the success of inclusive education is deep learning, which emphasizes active engagement, meaningful understanding, and the development of students’ critical thinking and collaborative skills. This study aims to describe the implementation of deep learning as a strategy to strengthen inclusive education for children with special needs in elementary schools. The study employed a qualitative approach with a descriptive research design. The research subjects consisted of classroom teachers, special assistant teachers, school principals, and students with special needs in inclusive elementary schools. Data were collected through observation, interviews, and documentation. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results showed that the implementation of deep learning was carried out through active, collaborative, contextual learning and differentiated instruction based on students’ needs. Deep learning was able to improve learning participation, social interaction, self-confidence, and understanding of learning materials among children with special needs. However, its implementation still faced several obstacles, such as limited teacher understanding, inadequate learning facilities, and challenges in managing inclusive classrooms. Therefore, support from schools, improvement of teacher competencies, and collaboration with parents are needed to optimize the implementation of inclusive education in elementary schools.